2018
DOI: 10.1109/mvt.2018.2814378
|View full text |Cite
|
Sign up to set email alerts
|

Fifth-Generation Control Channel Design: Achieving Ultrareliable Low-Latency Communications

Abstract: This article has been accepted for inclusion in a future issue of this journal. Content is final as presented, with the exception of pagination. 2 ||| 1556-6072/18©2018ieee ieee vehicular technology magazine | June 2018 This article has been accepted for inclusion in a future issue of this journal. Content is final as presented, with the exception of pagination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 11 publications
0
36
0
Order By: Relevance
“…In this case, the BLER of decoding the message is reduced to 2 . The success probability of delivering a message can be expressed as [4] = Figure 3(b) illustrates the reliability requirements for the control information to achieve the reliability of 1 − 10 −5 in downlink. The initial transmission round is performed with three different reliability targets.…”
Section: Urllc Requirements and Enablersmentioning
confidence: 99%
See 4 more Smart Citations
“…In this case, the BLER of decoding the message is reduced to 2 . The success probability of delivering a message can be expressed as [4] = Figure 3(b) illustrates the reliability requirements for the control information to achieve the reliability of 1 − 10 −5 in downlink. The initial transmission round is performed with three different reliability targets.…”
Section: Urllc Requirements and Enablersmentioning
confidence: 99%
“…For instance, the gNB would select more robust MCS for the transmission if the time budget is low, due to the buffer latency or missing the previous SR by the gNB. It is shown that the inclusion of such information can also relax the reliability constraint on the SR [4]. …”
Section: Scheduling Request (Sr)mentioning
confidence: 99%
See 3 more Smart Citations